Histórias em quadrinhos: um relato de experiência em um estúdio de artes - Martins, Andrey Marques (Brasil, 2024)
In contemporary times, comic books are present anywhere in the world as they are a means of mass production, taking on media or printed formats that are characterized according to the location, according to the culture of a given region. For this reason, this research sought to find out about the thematic approach present in comic books created by an arts studio located in the city of Parintins, Amazonas. The studio in question is made up of a collective of young artists who explore Amazonian themes through comics. The objective of this work revolves around describing the characteristics of the language of comic books created in an art studio. The descriptive method was used with a qualitative approach, which uses experience reports as a technique. The data production (collection) location took place on the premises of an arts studio. It is worth highlighting that an instrument called “Local Observational Subsidy Instrument” was used to produce (collect) data. Thus, it was found that the thematic approach of the work carried out on site focuses on the people of the Amazon through comic books. Therefore, culture is spread in order to positively influence art throughout the region, taking into account the description of the artistic process that passes through the hands of studio members who are trained by the creator and local coordinator. And, in this way, it becomes an essential process for the construction of comic books. In relation to the profile of those who frequent the studio in question, there are visual arts students; people from different artistic backgrounds and members of sociocultural movements and Non-Governmental Organizations with cultural interest. It is concluded, therefore, that the comics created in loco can be described as part of their involvement with the Amazonian scenario, as well as the culture of the people living in the municipality where the studio is located, as a way of disseminating knowledge, narrating stories related to the original people, caboclos and riverside dwellers of the Amazon region.